PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ANIMASI TERHADAP KOMPETENSI PENGETAHUAN IPA SISWA KELAS V - Purnawan, Indra (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
This study aims to determine the significant differences in knowledge of science students using learning-assisted Problem Based Learning model of Animation media with students who are taught using conventional learning. This research type is quasi experiment with Nonequivalent control group design. Population in this research is all student of class V at SD Gugus I Gusti Ngurah Rai East Denpasar year lesson 2016/2017 which amounts to 293 person.Pen sampel sample in this research done by technique of Purposive Sampling, first drawing class that eligible then drawing result given pretest to determine equality. After the equivalent on the basis of the t test the drawback is made to determine the experimental and control class. Data collection in this research is done by test method to collect data of science knowledge competence of student. Data value posttest knowledge of IPA is analyzed using t test. Based on the result of hypothesis test with t test, obtained value tcount2,75> ttabel2,00 at 5% significant level with dk 65 there H0 rejected and Ha accepted. This shows that there was a significant difference of science knowledge competence between students who were taught through the model of Learning-based Intercourse with animation with students who were taught by conventional learning in grade V SD Gugus I Gusti Ngurah Rai. In addition, based on the analysis with descriptive statistics obtained the average value of knowledge competence of science class of experiments 74.27> control class 68.09. Thus, it could be concluded that the application of Problem Based Learning model assisted by the media of Animation has an effect on the knowledge competence of science students of grade V SD Gugus I Gusti Ngurah Rai East Denpasar academic year 2016/2017.